Innovative Dakwah Strategies Through Social Media: Case Study of Islamic Communication Approaches in Indonesia - Hidayatullah, Riski Randa; Kamali, Muhammad Fakhri; T, Nur Asia (INJIES: Journal of Islamic Education Studies, 2024)
This study investigates innovative da'wah strategies through social media with a focus on Islamic communication approaches in Indonesia. The aim of this research is to explore the evolution of da'wah strategies, the impact of social media on religious communication, and the challenges and opportunities faced in the digital context. The research methods used include a literature review to understand the history of da'wah strategies and the impact of social media, as well as field research to analyse Islamic communication approaches used today. The research results show that technological advances have changed the landscape of da'wah, allowing wider access and more intense interaction between preachers and audiences. The implications of this research include recommendations for developing da'wah strategies that are more adaptive to technology, by utilizing artificial intelligence and blockchain technology to increase personalization and information security. The importance of ethics in conveying religious messages is also emphasized, emphasizing honesty, accuracy and respect for the diversity of society. This study makes an important contribution to the literature on digital da'wah and provides practical guidance for da'wah practitioners in utilizing social media effectively and responsibly